Penerapan Gamifikasi Berbasis Quizizz untuk Meningkatkan Motivasi Belajar Siswa dalam Pembelajaran Bahasa Inggris di SMAN 22 Makassar - Nurdzizati, Ainun; Hendra, Hendra; Yayha, Muh Alwia; Sulfirani, Siti; Alannasir, Wahyullah (JURNAL PENA, 2025)
This study aims to examine and analyze the influence of gamification elements such as point, badge, and leaderboard on students' learning motivation in English language learning using the Quizizz platform. A mixed methods approach with a descriptive design was employed. Quantitative data were collected through questionnaires completed by 55 students from SMAN 22 Makassar, while qualitative data were obtained through in-depth interviews with selected respondents. The results indicate that the point feature provides instant feedback that triggers students' intrinsic motivation to study more diligently. Badges offer symbolic recognition of students’ achievements, fostering a sense of being valued. Meanwhile, the leaderboard proves to be the most powerful in boosting motivation, as it creates healthy competition that encourages students to challenge themselves and improve their rankings. Therefore, integrating gamification elements such as those found in Quizizz can be an effective strategy for enhancing students’ learning motivation, especially in the context of English language learning at the senior high school level. Keywords:  Quizizz, learning motivation, point, badge, leaderboard. References Alsawaier, R. S. (2018). The effect of gamification on motivation and engagement. The International Journal of Information and Learning Technology, 35(1), 56–79. Amrullah, M. K., & Muin, M. F. (2023). Motivasi Ektrinsik pada Siswa Smp IT Insan Mulia Batanghari. Journal of Media and Pedagogical Practices, 1(01), 33–40. Bai, S., Hew, K. F., & Huang, B. (2020). Does gamification improve student learning outcome? Evidence from a meta-analysis and synthesis of qualitative data in educational contexts. Educational Research Review, 30, 100322. Gay, L. R., Mills, G. E., & Airasian, P. W. (2020). Educational research: Competencies for analysis and applications (12th ed.). Pearson. Kuo, M.-S., & Chuang, T.-Y. (2016). How gamification motivates visits and engagement for online academic dissemination–An empirical study. Computers in Human Behavior, 55, 16–27. Lenggono, B., & Yuzarion, Y. (2020). Motivasi berprestasi pada siswa SMA dalam perspektif Islam [PhD Thesis, Universitas Ahmad Dahlan]. https://www.neliti.com/publications/482140/motivasi-berprestasi-pada-siswa-sma-dalam-perspektif-islam Li, M., Ma, S., & Shi, Y. (2023). Examining the effectiveness of gamification as a tool promoting teaching and learning in educational settings: A meta-analysis. Frontiers in Psychology, 14, 1253549. Maslow, A. H. (2022). A theory of human motivation. Lushena Books. (Original work published 1943) Mutiara, P., Fauzi, A., Wahyuni, A. D., Adisti, A. A., Kurniasi, F., & Afifi, S. T. (2022). Pengaruh Pelatihan, Motivasi dan Reward Terhadap Kinerja Karyawan. JIM: Jurnal Ilmu Multidisiplin, 1(3), 636–646. Shen, Z., Lai, M., & Wang, F. (2024). Investigating the influence of gamification on motivation and learning outcomes in online language learning. Frontiers in Psychology, 15, 1295709. Su, C., & Cheng, C. (2015). A mobile gamification learning system for improving the learning motivation and achievements. Journal of Computer Assisted Learning, 31(3), 268–286. https://doi.org/10.1111/jcal.12088 SUNARTI, S. (2021). Pengaruh Pola Komunikasi Orang Tua Dalam Keluarga Terhadap Motivasi Belajar Pedserta Didik Di Sd 32 Buakang [PhD Thesis, INSTITUT AGAMA ISLAM MUHAMMADIYAH SINJAI]. http://repository.uiad.ac.id/id/eprint/897/1/SKRIPSI%20SUNARTI.pdf Urhahne, D., & Wijnia, L. (2023). Theories of Motivation in Education: An Integrative Framework. Educational Psychology Review, 35(2), 45. https://doi.org/10.1007/s10648-023-09767-9 Velázquez-García, L., Longar-Blanco, M. D., Cedillo-Hernández, A., & Bustos-Farías, E. (2024). Gamification in the classroom: Motivating higher education students using digital badges. International Journal of Learning and Teaching, 10(4), 532–538. Widodo, U., & Winarti, A. (2019). Faktor-faktor motivasi dalam pembelajaran bahasa inggris. Jurnal Pendidikan, Sains Sosial, Dan Agama, 5(2), 48–64.